2016
DOI: 10.1002/ange.201602150
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework for Emulsifying Carbon Dioxide and Water

Abstract: Forming emulsions of carbon dioxide (CO2) and water can largely expand the utility of CO2. Herein we propose for the first time the utilization of a metal–organic framework (MOF) for emulsifying CO2 and water. Owing to the hybrid composition, MOF particles can easily assemble at the CO2/water interface to create a rigid protective barrier around the dispersed droplet. The MOF‐stabilized CO2 and water emulsion has exceptional stability compared to those emulsions stabilized by surfactants or other solids. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Figure 7 also shows that the material stabilized by MIL‐100(Fe) holds a distinctly smaller void size than that of stabilizing by pure PVA. This interesting effect has also explained that CO 2 and water emulsion downsize the MOFs to minuscule nanocrystals and then march the assembly of these nanocrystals to superstructures, 16 for another high‐pressure CO 2 pushes forward the formation of minuscule particles by the viscosity‐lowering effect 54 …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Figure 7 also shows that the material stabilized by MIL‐100(Fe) holds a distinctly smaller void size than that of stabilizing by pure PVA. This interesting effect has also explained that CO 2 and water emulsion downsize the MOFs to minuscule nanocrystals and then march the assembly of these nanocrystals to superstructures, 16 for another high‐pressure CO 2 pushes forward the formation of minuscule particles by the viscosity‐lowering effect 54 …”
Section: Resultsmentioning
confidence: 96%
“…Due to the amphiphilic composition, MOF particle is capable of aggregating in the CO 2 /water interface to form a firm barrier around the dispersed droplet (see microscopic diagrams in Figure 2). 16 The addition of PVA before polymerization is critical because the addition of organic monomers and the increase of temperature will reduce the stability of the emulsion 12,53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An early successful example is enantioselectivity enhancement obtained through assembling amphiphilic molecular catalysts at the biphasic interface 22,23 , but this strategy is not suited for reactions involving solid particle catalysts. Recently, Pickering (particle-stabilized) emulsions have been shown to be an ideal platform for the assembly of solid particle catalysts at biphasic interfaces because of the high adsorption energy of a particle at the interfaces [24][25][26][27][28][29][30][31][32][33][34][35][36] . Although enhanced catalysis rates have been achieved in diverse reactions compared with conventional biphasic or monophasic systems, harnessing unique properties of Pickering emulsion interfaces to tune catalytic selectivity has scarcely been reported so far, except for the case where the selectivity was improved due to the phase-selective partitioning of reactants in a biphasic system instead of the salient features of liquid-liquid interfaces 37 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that some MOFs can emulsify two immiscible liquids, like water and oil, water and hydrophobic ionic liquid, water and supercritical CO2, to produce particle-stabilised Pickering emulsions. [21][22][23][24][25][26][27] Analogous to traditional emulsifiers, the MOF nanoparticles can assemble at the interface of the two immiscible phases to stabilize the emulsion droplets against coalescence. Interestingly, the structures and properties of the emulsions can be easily modulated by adjusting the metal ions and organic ligands of MOFs owing to their designable and tunable features.…”
Section: Introductionmentioning
confidence: 99%